The Effectiveness of Using Human Resource Information System on the Performance of Employees at Hermina Arcamanik Hospital - Sani Fitriyani; Kelvin Herlambang H; Muhammad Prakarsa Al Qadr Saleh; Candra Mecca Sufyana (Greenation Research & Yayasan Global Resarch National, 2024)
To remain competitive in the health industry and streamline performance, an efficient human resource management system is essential. This research employs a qualitative approach with a case study design, gathering data through semi-structured interviews and direct observation. The findings reveal that Human Resource Information System (HRIS XPRESSO), implemented in 2019, offers features such as managing employee personal data, training records, and integrating recruitment and payroll processes. This system has significantly enhanced HR department performance by simplifying data access and reducing manual processes. However, challenges such as large file rejections, server disruptions, and limited access outside the hospital were identified. To enhance effectiveness, feature improvements and access adjustments are necessary. In conclusion, HRIS XPRESSO has proven effective in boosting HR operational efficiency but requires ongoing evaluation and institutional reforms to address existing challenges and fully leverage its benefits for the organization.